A new species of Dracoderes (Kinorhyncha: Dracoderidae) from Korea provides further support for a dracoderid-homalorhagid relationship - Thomsen, Vibe G.; Rho, Hyun Soo; Kim, Dongsung; Sørensen, Martin V. (Zootaxa, 2013)
A new kinorhynch species, Dracoderes nidhug nov. sp., is described from the East Sea, at 160 m depth, off Uljin, Korea. The new species is the fourth that can be assigned to the genus, and is recognized by the presence of dorsal spines on seg-ments 3 to 9 (alternatingly displaced to more paradorsal positions on segments 3 to 8), subdorsal tubules on segment 2, lateroventral tubules on segments 2, 5 and 10, and lateral accessory tubules on segment 8. The new species shows two longitudinal, intracuticular markings on the ventral side of segment 1, which could be interpret as rudimentary plate joints, corresponding to the articulations found on the sternal plates of segment 1 in species of Pycnophyes and Kinorhynchus. The finding brings further support to a closer relationship between Dracoderes and homalorhagid kinorhynchs.